Acrodermatitis due to zinc deficiency after combined vertical gastroplasty with jejunoileal bypass: case report - Cunha, Selma Freire de Carvalho; Gonçalves, Gilson Antônio Pereira; Marchini, Julio Sérgio; Roselino, Ana Maria Ferreira (São Paulo Medical Journal, 2012)
CONTEXT: Nutritional complications may occur after bariatric surgery, due to restriction of food intake and impaired digestion or absorption of nutrients. CASE REPORT: After undergoing vertical gastroplasty and jejunoileal bypass, a female patient presented marked weight loss and protein deficiency. Seven months after the bariatric surgery, she presented dermatological features compatible with acrodermatitis enteropathica, as seen from the plasma zinc levels, which were below the reference values (34.4 mg%). The skin lesions improved significantly after 1,000 mg/day of zinc sulfate supplementation for one week. CONCLUSIONS: The patient’s evolution shows that the multidisciplinary team involved in surgical treatment of obesity should take nutritional deficiencies into consideration in the differential diagnosis of skin diseases, in order to institute early treatment.